Anthropometric profile of the brazilian male judo team: cross-sectional study - André Luíz Lopes; Gustavo dos Santos Ribeiro; Bruno Costa Teixeira; Randhall Bruce Carteri; Paulo Cavalcante Muzy; André Pontes-Silva (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: To describe the anthropometric profile of the Brazilian judo team and compare it with physically active individuals. Methods: Cross-sectional study. The sample consisted of eight high-performance athletes from a male judo team. This sample included judokas from four categories: extra-lightweight, middle-lightweight, light-weight, and middle-heavyweight. All athletes had experience in international tournaments and had won Pan-American, World, and Olympic medals. Data were analyzed with GraphPAD Prism 5.01. Anthropometric indices, body composition and somatotype were analyzed by Mann-Whitney test with 95% confidence (significant p<0.05). Cohen's d effect size was used to determine the effect size between variables that were significantly different. Data are presented as median, minimum and maximum values (descriptive variables) or phantom z-scores (proportionality). Results: The data indicate a very large effect size for the bone-muscle index (d = 2.72) and the mesomorphic phenotype (d = 1.33) in judokas and students. Large effect sizes were observed for muscle mass (d = 1.12), fat mass (d = -0.91), and the ectomorphic phenotype (d = -0.88). Moderate between-group effect sizes were observed for skinfolds (d = -0.71) and arm muscle area (d = 0.63). Conclusions.